Adding Pharmacists to Primary Care Teams Increases Guideline-Concordant Antiplatelet Use in Patients with Type 2 Diabetes: Results from a Randomized Trial. (January 2013) - Gilani, Fizza; Majumdar, Sumit R; Johnson, Jeffrey A; Tsuyuki, Ross T; Lewanczuk, Richard Z; Spooner, Richard; Simpson, Scot H
BACKGROUND: Antiplatelet therapy is recommended as part of a strategy to reduce the risk of cardiovascular events in patients with type 2 diabetes. However, compliance with these guideline-recommended therapies appears to be less than ideal. OBJECTIVE: To assess the effect of adding pharmacists to primary care teams on initiation of guideline-concordant antiplatelet therapy in type 2 diabetic patients. METHODS: Prespecified secondary analysis of randomized trial data. In the main study, the pharmacist intervention included a complete medication history, limited physical examination, provision of guideline-concordant recommendations to the physician to optimize drug therapy, and 1-year follow-up. Controls received usual care without pharmacist interactions. Patients with an indication for antiplatelet therapy, but not using an antiplatelet drug at randomization were included in this substudy. The primary outcome was the proportion of patients using an antiplatelet drug at 1 year. RESULTS: At randomization, 257 of 260 study patients had guideline-concordant indications for antiplatelet therapy, but less than half (121; 47%) were using an antiplatelet drug. Overall, 136 patients met inclusion criteria for the substudy (71 intervention and 65 controls): 60% were women, with mean (SD) age 58.0 (11.9) years, diabetes duration 5.3 (6.0) years, and hemoglobin A1c 7.6% (1.5). Sixteen (12%) had established cardiovascular disease at enrollment. At 1 year, 43 (61%) intervention patients and 15 (23%) controls were using an antiplatelet drug (38% absolute difference; number needed to treat, 3; relative increase, 2.6; 95% CI 1.5–4.7; p < 0.001). Of these 58 patients, 52 (90%) were using aspirin 81 mg daily. CONCLUSIONS: Adding pharmacists to primary care teams significantly and substantially increased the proportion of type 2 diabetic patients using guideline-concordant antiplatelet therapy.